2016
DOI: 10.1111/jmwh.12499
|View full text |Cite
|
Sign up to set email alerts
|

Labor and Birth Care Satisfaction Associated With Medical Interventions and Accompaniment During Labor Among Chilean Women

Abstract: This study is one of the first to provide empirical evidence that maternal patient satisfaction is negatively affected by many common obstetric procedures in the Latin American context. These findings are consistent with World Health Organization recommendations regarding judicious and necessary, rather than routine, use of obstetric interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 36 publications
1
33
1
15
Order By: Relevance
“…Studies indicated maternal satisfaction with care provided during labor and childbirth varies in different areas; 67% in Sweden [23], 68.8% in Italy [24] and 49.4% had optimal and 29% had adequate satisfaction in Chile [25,26]. From other studies done in Nepal (86%) [27], Bheri Zonal Hospital Nepal (89.8%) [28], Jordan 17.8% [29], Egypt (78.5%) [30] and 92.5% in southern Mozambique [31] women reported as being satisfied with the care during childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicated maternal satisfaction with care provided during labor and childbirth varies in different areas; 67% in Sweden [23], 68.8% in Italy [24] and 49.4% had optimal and 29% had adequate satisfaction in Chile [25,26]. From other studies done in Nepal (86%) [27], Bheri Zonal Hospital Nepal (89.8%) [28], Jordan 17.8% [29], Egypt (78.5%) [30] and 92.5% in southern Mozambique [31] women reported as being satisfied with the care during childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1995, the World Health Organization (WHO) has developed guidelines to limit the routine episiotomy, stating that only fetal distress is recommended as an indication for episiotomy in obstetric and midwifery guidelines . Complications associated with episiotomy include negative birth experience, unsatisfactory anatomic results, increased postpartum blood loss and pain, discomfort of the wound and sutures, higher rates of infection and dehiscence, urinary incontinence, sexual dysfunction, and possible increased risk of perineal lacerations in subsequent deliveries . Restrictive episiotomy (“only if needed”) is significantly beneficial for women over a routine approach (“part of routine management”).…”
Section: Introductionmentioning
confidence: 99%
“…The WHO recommends a companion of choice during labor and birth for the improvement of maternal and perinatal outcomes and women's satisfaction with health care services (1). Having a labor companion has been shown to impact positively on women's experience of care (1,11). Given its importance, we attempted to understand the prevalence of this practice in LAC countries.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were conducted mainly in Brazil, and a few in Chile, where companion of choice is implemented. Women and their companions reported a positive experience, based on feelings of physical and emotional well-being, less fear and pain, and increased self-confidence (9)(10)(11). Health teams also reported a positive experience; however, reluctance to allow companionship was also reported (12)(13)(14).…”
Section: Current Challenges and Gaps For Latin America And The Caribbeanmentioning
confidence: 99%